Using Multiattribute Analysis to Predicting Effective Porosity of Yamama Formation in Nasriya Oilfield Southern Iraq - Khorshid, Salman Z.; Al-Sharaa, Ghazi H.; Mohammed, Maha F. (Iraqi Journal of Science, 2018)
Emerge application was used in Hampsson-Russell programs and that uses a combination of multiple 3D or 2D seismic attributes to predict some reservoir parameter of interest. In this research used the seismic inversion technique was performed on post-stack three dimensions (3D) seismic data in Nasriya oilfield with five wells and then used this results in Emerge analysis (training and application) were used to estimate reservoir properties (effective porosity) with multiattribute analysis derive relations between them at well locations. The horizon time slice of reservoir units of (Yb1, Yb3 and Yc) of Yamama Formation was made for property (effective porosity) to confirm match results and enhancement trends within these units. Because of the good prospects of the oil in the rocks of Cretaceous generally and Yamama Formation specially in the Nasriya oilfield and in view of the economic importance of Yamama Formation, which is considered as important formation that contains hydrocarbon accumulation, and one of the most important and oil production reservoirs in southern Iraq.